2020
DOI: 10.1007/s00417-020-04603-0
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal intraocular lenses and retinal diseases

Abstract: Purpose Multifocal intraocular lenses (MIOLs) are often discouraged in patients with or at risk of retinal disorders (including diabetic retinopathy, age-related macular degeneration, and epiretinal membranes), as MIOLs are believed to reduce contrast sensitivity (CS). Concerns with MIOLs have also been raised in individuals with visual field defects, fixation instability or eccentric preferred retinal locations. The aim of this study is to review the influence of MIOL on quality of vision in patients with ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 64 publications
2
35
0
3
Order By: Relevance
“…The results of this retrospective study are similar in terms of mean gain in CDVA to those recorded in patients with monofocal IOL implants [18][19][20][21], thus mitigating one of the main concerns with respect to implantation of multifocal IOLs which is the rationale of this study and is consistent with the outcomes observed for multifocal IOL implants in eyes with other macular diseases, such as aged-related macular degeneration and diabetic retinopathy [12]. Our observation seems to be more associated with macular SD-OCT ndings in the ellipsoid zone ( IS/OS junction) recovery, as observed and discussed by Inoue and Morita [6,22].The mean UNVA results also improved signi cantly after the decrease recorded at diagnosis of ERM, which is also associated in our study with complete recovery of the ellipsoid zone.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of this retrospective study are similar in terms of mean gain in CDVA to those recorded in patients with monofocal IOL implants [18][19][20][21], thus mitigating one of the main concerns with respect to implantation of multifocal IOLs which is the rationale of this study and is consistent with the outcomes observed for multifocal IOL implants in eyes with other macular diseases, such as aged-related macular degeneration and diabetic retinopathy [12]. Our observation seems to be more associated with macular SD-OCT ndings in the ellipsoid zone ( IS/OS junction) recovery, as observed and discussed by Inoue and Morita [6,22].The mean UNVA results also improved signi cantly after the decrease recorded at diagnosis of ERM, which is also associated in our study with complete recovery of the ellipsoid zone.…”
Section: Discussionsupporting
confidence: 83%
“…A reduction in contrast sensitivity has been reported with diffractive trifocal IOLs [10] and many authors therefore recommend avoiding implantation of a multifocal IOL in patients with macular impairments such as ERM [11,12]. However others have reported good visual outcomes with implantation of multifocal IOL in patients with age-related macular degeneration and diabetic retinopathy [12]. One population-based prevalence study on 4439 subjects with an age ≥ 40 years has shown a 10-year incidence of ERM of 8.4% [13].…”
Section: Introductionmentioning
confidence: 99%
“…Erkrankungen der Makula bzw. der Netzhaut stellen zwar keine absoluten Kontraindikationen für die Implantation multifokaler Intraokularlinsen (MIOL) dar [1,2]. Dennoch werden diese in solchen Fällen selten implantiert, meist weil befürchtet wird, dass Patienten, die bereits eine verminderte Sehleistung haben, durch die Multifokalität der implantierten IOL zusätzlich eingeschränkt werden [3].…”
Section: Selection Of Intraocular Lenses For Patients With Maculopathiesunclassified
“…Dennoch werden diese in solchen Fällen selten implantiert, meist weil befürchtet wird, dass Patienten, die bereits eine verminderte Sehleistung haben, durch die Multifokalität der implantierten IOL zusätzlich eingeschränkt werden [3]. Die durch MIOLs vermeintlich hervorgerufene Herabsetzung der Kontrastempfindlichkeit wird oft angeführt, obwohl es in der Literatur selbst bei gesunden Augen widersprüchliche Ergebnisse zur Reduktion der Kontrastempfindlichkeit durch MIOLs gibt, wie Grzybowski et al [2] berichten.…”
Section: Selection Of Intraocular Lenses For Patients With Maculopathiesunclassified
“…Modern surgical implantation of multifocal intraocular lenses (MIOLs) is an option for optical correction of presbyopia that exists before cataracts are present. [3][4][5] The procedure is referred to as "clear lens extraction (CLE)", and advances in this technology have enabled it to become a popular refractive procedure. [6][7][8][9][10] MIOLs can induce aberrant light perception disturbances; 11 thus, motivation to achieve spectacle freedom must outweigh the potential adverse effects.…”
Section: Introductionmentioning
confidence: 99%